The Darling Dahlias and the naked ladies - Albert, Susan Wittig (Albert, Susan Wittig. Darling Dahlias mysteries., 2011)
The Dahlias become suspicious of the newest visitors to Depression-era Darling, Alabama, rumored to be the Naughty and Nice Sisters from the Ziegfeld Frolic, who specialize in dancing nearly naked, and dig for the truth when one of the pair denies the association.